Pelatihan Penanganan Awal pada Kegawatdaruratan Kejang Demam pada Anak Dengan Teknik Tepid Water Sponge di Balai Desa Ledug Kembaran Banyumas - Hapsari, Amelya Prabawati; Sukmaningtyas, Wilis; Sekar Siwi, Adiratna (Universitas Baiturrahim, 2025)
Febrile convulsions are seizures that occur in children aged 6 months to 5 years who experience an increase in body temperature above 38 ℃. Tepid water sponge is a warm compress with a wipe technique given to patients who have high fever to reduce or reduce body temperature, so that with controlled body temperature will reduce the risk of seizures. The purpose of this community service is to implement the provision of training so as to increase the knowledge and skills of mothers in the initial handling of febrile seizures in children with tepid water sponge techniques. The methods used in this training activity are pre-test and post-test questionnaire methods, lectures, demonstrations, and discussions after the implementation of training activities. A total of 30 mothers in Ledug Village on 5 June 2024 became participants who were given a pre test and post test to determine their level of knowledge. The results of measuring the knowledge and skills of mothers after the training showed that the majority of mothers could understand well related to the management of early management of febrile seizures as many as 21 people (70%). Evaluation of skill level was also given to the parents. The results showed that before the training, all 28 participants fell into the incompetent category. After the training, there was an increase in skills with the majority being in the highly competent category as many as 13 people (42.8%). This activity proved to be effective in improving the knowledge and skills of parents in Ledug Village about the initial handling of febrile seizures in children.